AN INVESTIGATION ON ENGINE PERFORMANCE AND EMISSIONS OF USING MICROALGAE AND MICROALGAE-ETHANOL BLENDS - Duran, Gonenc; Donmez, Muhammed; Ilkilic, Cumali (Turkish Soc Thermal Sciences Technology, 2023)
Increasing use of fossil fuels with the increase in industrialization, number of vehicles and population causes problems such as energy requirement and emissions. In this study, biodiesel production was carried out by transesterification using microalgae oil, methanol, and sodium methylate as catalyst which can be used in internal combustion engines. In today's trend studies of Microalgae has been preferred because of its growth environment that does not require the use of arable land and its good raw material/oil conversion ratio. In addition, the effect of fuels on engine performance and emissions was investigated by obtaining a mixture of obtained biodiesel and ethanol at different rates. Experiments were carried out at full load in the engine speed range of 1000-3000 rpm. The maximum engine torque is obtained at 1800 rpm, while the maximum power is obtained at 2600 rpm. For biodiesel mixed with 15% ethanol, there was a 0.86% increase in torque at 1800 rpm compared to diesel, and a decrease of 0.42% in power at 2600 rpm. The emission values resulting from the combustion of biodiesel and ethanol blended fuels have decreased considerably compared to the use of diesel fuel. Thus, emissions harmful to humans and the environment, especially carbon dioxide emissions that cause global warming, have decreased significantly.
MIKROALG VE MIKROALG – ETANOL KARIŞIMLARI KULLANIMININ MOTOR PERFORMANS VE EMISYONLARI ÜZERINE BIR INCELEME
Keywords: ethanol; microalgae; biodiesel; chlorella protothecoides; methyl ester